2010
DOI: 10.1007/s10875-009-9363-z
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like Receptor Expression on Peripheral Blood Mononuclear Cells in Asthmatics; Implications for Asthma Management

Abstract: TLR-mediated inflammatory signals contribute to the development and severity of asthma and are not reduced by glucocorticoid treatment, which suggests that a TLR-specific antagonist and glucocorticoid are required for the effective control of airway inflammation in asthmatics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 22 publications
1
14
1
7
Order By: Relevance
“…In severe asthma, allergen challenge only increased the expression of Tlr2 and allergen sensitization and challenge significantly increased Tlr1 expression when compared to sensitized only mice. These results are supported by data from animal and human studies which have shown that Tlr2/Tlr1 heterodimers can play both pro- and anti-inflammatory roles in allergic asthma [16, 35]. Interestingly, allergen sensitization and challenge decreased Tlr3 expression in both models.…”
Section: Discussionsupporting
confidence: 62%
“…In severe asthma, allergen challenge only increased the expression of Tlr2 and allergen sensitization and challenge significantly increased Tlr1 expression when compared to sensitized only mice. These results are supported by data from animal and human studies which have shown that Tlr2/Tlr1 heterodimers can play both pro- and anti-inflammatory roles in allergic asthma [16, 35]. Interestingly, allergen sensitization and challenge decreased Tlr3 expression in both models.…”
Section: Discussionsupporting
confidence: 62%
“…Chun and colleagues (19) recently profiled TLR protein expression on peripheral blood mononuclear cells in asthmatics and observed that, unlike TLR1, TLR2, and TLR9, TLR6 expression was significantly lower in asthmatic patients compared with controls. Moreover, this receptor has been associated with decreased susceptibility for the development of atopic asthma (16).…”
Section: Resultsmentioning
confidence: 99%
“…TLRs activate transcription factors that increase expression of a variety of inflammatory markers (35). Although TLRs are most often associated with infectious diseases, they have more recently been associated with noninfectious conditions such as asthma (36), inflammatory bowel disease (37), rheumatoid arthritis (38), and T1D. There are 12 known TLRs with various specificities; TLR2 and TLR4 have been implicated in T1D.…”
Section: Tlrsmentioning
confidence: 99%